2007
DOI: 10.1007/s00134-007-0739-3
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of muscle StO2 in septic patients

Abstract: Altered recovery in StO(2) after an ischemic challenge is frequent in septic patients and more pronounced in the presence of shock. The presence and persistence of these alterations in the first 24[Symbol: see text]h of sepsis are associated with worse outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
246
5
12

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(280 citation statements)
references
References 47 publications
17
246
5
12
Order By: Relevance
“…14,15,25,26 In our small series of patients, the microcirculation was moderately to severely compromised, in line with previous studies of patients with severe sepsis and septic shock. 14,22,23 For example, Creteur et al 22 reported NIRS ascending slope values of 2.3 ± 1.3%Ásec -1 in patients with septic shock, a value similar to our findings. Skarda et al 23 found NirVO 2 values of 97 ± 36 U, again in the range seen in our patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…14,15,25,26 In our small series of patients, the microcirculation was moderately to severely compromised, in line with previous studies of patients with severe sepsis and septic shock. 14,22,23 For example, Creteur et al 22 reported NIRS ascending slope values of 2.3 ± 1.3%Ásec -1 in patients with septic shock, a value similar to our findings. Skarda et al 23 found NirVO 2 values of 97 ± 36 U, again in the range seen in our patients.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in line with other studies in sepsis that relate the severity of microcirculatory abnormalities to the severity of disease. 14,22,29 In conclusion, these data suggest that microcirculatory abnormalities are present in patients with acute lung injury associated with severe influenza A (H1N1) infection independently of any bacterial co-infection.…”
Section: Steroidsmentioning
confidence: 73%
See 1 more Smart Citation
“…One can also imagine a different behavior of cells in chronic hypoxia, further amending the dynamic curves (ie, O 2 consumption rate, reactive hyperhemia time, and time interval) compared with the princeps work during sepsis. 4 Accordingly, elevated venous pressure has been related to impaired microvascular tissue perfusion. 5 Thus, a possible modification of post-capillary venous vessel capacitance would obscure NIRS-VOTderived values.…”
Section: Near-infrared Spectroscopy With Vascular Occlusion Test May mentioning
confidence: 99%
“…The specific effect of transfusion was not evaluated in this study, however, as the investigation was designed to assess the overall bundle rather than its component parts. Using Near Infrared Spectroscopy (NIRS) or Sidestream Dark Field (SDF), several investigators have reported that microcirculation is markedly altered in sepsis, that these alterations are more severe in nonsurvivors than in survivors, that persistent microvascular alterations are associated with development of multiple organ failure and death, and that microvascular alterations are the most sensitive and specific predictor of outcome in septic patients [91][92][93][94][95][96][97].…”
Section: Within 6 Hours Of Severe Sepsismentioning
confidence: 99%